Formulation and evaluation of Acyclovir compressed lozenges - Dalya Badry Khudhair; Wedad K. Ali (College of Pharmacy / Mustansiriyah University, 2022)
Lozenges are formulations of solid dosage form which tend to liquefy in mouth or pharynx. They could be consisting of one or more drugs in a flavored and sweetened base. They are recommended to treat local mouth or pharynx irritation or infection, or they may be used also for systemic combi-   nation of two drugs (Acyclovir and Lidocaine) by pressed coated tablet lozenges. Thus, the lozenges will have both antiviral and local anesthetic effects suitable for the treatment of virus that infects oral cavity.   In this study, nine formulations of acyclovir compressed tablet lozenges were prepared to investigate the effects of type and concentration of binders (gelatin, acacia, and tragacanth) on physical appearance, weight variation, hardness, thickness, friability, dissolving , drug content and in vitro released of drug. Compressed tablet lozenges formula F4 contening (Acacia 10%) as binder was successfully prepared and has been selected as optimum formula  since it released 98% of drug after 45 min, as compared to other formulas.